The Role of AI Technology in Advancing Education, Empowerment, and Entrepreneurship for Afghan Women - Alizada, Zohra; Fatima Mohammadi; Fatima Sahibzada (RADINKA JAYA UTAMA PUBLISHER, 2025)
Artificial Intelligence (AI) has emerged as a transformative mechanism for expanding educational access, enhancing digital empowerment, and fostering entrepreneurial engagement among marginalized populations. This study investigates the specific role of AI technologies—such as generative AI tools, AI-powered language translation applications, adaptive learning platforms, and automated chatbots—in supporting Afghan women’s education and socio-economic participation. Employing a quantitative descriptive research design, data were collected from 150 female students across four faculties (Computer Science, Business Administration, Education, and Sharia & Law) at Vision Online University. Results show that 77% of participants perceive AI as significantly improving learning opportunities for women, particularly through personalized learning support and language-based assistance. Additionally, 69% reported that AI tools enhanced their digital skills, while 62% indicated that AI applications increased their interest in online business creation and entrepreneurial activities. Despite these benefits, respondents identified major barriers including limited access to digital devices (58%), unstable internet connectivity (64%), and low digital literacy (52%). The findings reveal AI’s multidimensional impact in strengthening knowledge, autonomy, and economic participation for Afghan women. The study underscores the need for inclusive digital infrastructure and culturally sensitive implementation strategies to fully leverage AI as a sustainable driver of gender equality and socio-economic development in Afghanistan.